2016
DOI: 10.4018/ijitbag.2016010101
|View full text |Cite
|
Sign up to set email alerts
|

How Business Strategy and Technology Impact the Role and the Tasks of CIOs

Abstract: The authors investigate the determinants of CIOs' organizational role and tasks. They first review previous studies, which they classify as either evolutionary or CIO role studies. They consider them to be characteristic to the usage of certain technologies or certain periods of times. The authors modify Leavitt's well-known organization diagnostic model to describe factors that shape the role and the tasks of CIOs over time, industries and technologies. They validate the model from interviews with 36 CIOs wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…We also learned from this case and from earlier CIO studies (e.g. Dahlberg, Hokkanen & Newman, 2016;Peppard, Edwards & Lambert 2011) that CIOs are under a great deal of stress due to constant changes in their work. CIOs often work with all units and functions in an organization and encounter conflicting demands and perceptions about the role of IT in business and their work with too few tools and employees to cope with the various demands.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…We also learned from this case and from earlier CIO studies (e.g. Dahlberg, Hokkanen & Newman, 2016;Peppard, Edwards & Lambert 2011) that CIOs are under a great deal of stress due to constant changes in their work. CIOs often work with all units and functions in an organization and encounter conflicting demands and perceptions about the role of IT in business and their work with too few tools and employees to cope with the various demands.…”
Section: Discussionmentioning
confidence: 74%
“…We selected the case company among those that had been interviewed already for another CIO study (Dahlberg, Hokkanen & Newman, 2016). From that study, we found a pair of CIOs who were parties on the opposite sides of a major M&A transaction.…”
Section: Methodology and The Casementioning
confidence: 99%
See 1 more Smart Citation
“…Due to the component “technology,” the model was especially adopted by research about knowledge management and information systems in the previous years (e.g. Dahlberg et al, 2016; Liao and Teo, 2018; Lyytinen and Newman, 2008; Sluyts et al, 2010; Zhao and Yang, 2017). Furthermore, it was expanded and further developed in different ways (e.g.…”
Section: Research Contextmentioning
confidence: 99%
“…Furthermore, it was expanded and further developed in different ways (e.g. Dahlberg et al, 2016; Rockart and Scott Morton, 1984). Although the model does not explain the particular steps for organizational change, it is useful to emphasize the complexity of a change process.…”
Section: Research Contextmentioning
confidence: 99%